(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study was carried out to examine the effect of aerobic training program applied to smokers and non-smokers on anaerobic power, balance and speed performances. For this purpose, a total of 30 male volunteers between the ages of 18-26 were included. A total of 30 healthy male volunteers participated. These individuals were selected from those who attended the aptitude test preparation courses in Gaziantep. According to this analysis, those who were addicted to cigarettes were determined as the smokers group (n: 15), and those who had never smoked were determined as the non-smokers group (n: 15). A two-hour aerobic training program, three days a week, was applied to both groups for eight weeks. Before the training and after the end of the course, repeated anaerobic sprint test, flamingo balance test and 30 meters sprint test were applied. As a result of the findings, in the analysis of the difference between the pre-test and post-test of the smoking and non-smoking groups, there was no statistical significance in the values of the smoking group (p>0.05); In the speed and raster tests of the non-smoker group, a significant difference was found in favor of the post-test, and between the groups in favor of the non-smoker group (p<0.05). As a result, we can say that the eight-week aerobic training program applied to smokers and non-smokers positively changes and improves the balance and speed levels of non-smokers.